Explaining US–China economic imbalances: a social perspective. Issue 3 (2nd July 2016) - Sheng, Li
Abstract: China has witnessed a continual drop in the labour income share of its gross domestic product (GDP) and a steep rise in income that has caused a savings glut and high investments. China's shrinking domestic demand indicates that its output growth must increasingly rely on expanded manufacturing exports to the US. China's state accommodation for US offshoring further aggravates trade imbalances between the two countries. The United States is also experiencing a rise in social inequality associated with a decline in savings that is a fundamental cause of its current-account deficit with China. The swelling US service sector interacts with a high ratio of consumption to income, and the liberal US policy for cost outsourcing to China has a complicated impact on employment and an adverse effect on inequality.